Students’ Views on the Use of the BoldVoice Application in Enhancing English Speaking Skills - Qorri Fadhilah; Ernita Daulay (Universitas Negeri Semarang, 2025)
Background – Speaking is one of the most challenging English skills for students due to limited practice, anxiety, and difficulties in pronunciation and intonation. The integration of technology through AI-based tools such as BoldVoice offers new opportunities for improving speaking performance in formal education. Purpose – This study aims to explore students’ perceptions of the BoldVoice application in enhancing their English-speaking skills, specifically focusing on pronunciation, intonation, and speaking confidence. Method/Approach – This qualitative descriptive research involved 30 ninth-grade students at SMP Al-Hidayah, Medan, selected through purposive sampling. Data were collected using questionnaires with a four-point Likert scale and semi-structured interviews, then analyzed descriptively and thematically. Findings – The results show that the BoldVoice application is perceived positively by students in helping them improve their pronunciation and intonation, as well as in building their confidence to speak English. Real-time feedback and interactive features were found effective in supporting students’ learning, although some still faced challenges in spontaneous speaking. Conclusions – The BoldVoice application can serve as a useful supplementary tool in English language learning, especially in improving phonetic accuracy and student motivation to speak. Novelty/Originality/Value – The novelty of this study lies in its focus on junior high school students within a formal classroom setting, which has rarely been explored in previous research involving AI-based language learning tools.